Possibility Assessment of Reservoir Expansion in the Conterminous United States - Hadi Heidari; Baptiste Francois; Casey Brown (Hydrology, 2022)
Reservoir expansion is commonly considered an adaptation strategy to attenuate water shortage conditions. In many locations in the United States, there are ongoing discussions about the effectiveness and feasibility of reservoir expansion with regard to the growing drought conditions and a consequent significant decrease in surface water. This study investigates if the expansion of the existing Unites States reservoirs should be still considered an effective and adequate management solution to cope with water shortages. To this end, we have defined three reservoir expansion metrics to assess the efficiency, feasibility, and usefulness of increasing the storage capacity of 304 reservoirs across the conterminous United States (CONUS). The efficiency metric is defined as the ratio of reservoir average storage to maximum active storage. The feasibility metric is defined as the ratio of reservoir average annual inflow to maximum active storage and the usefulness metric is described as the ratio of the reservoir average annual excess inflow (average annual inflow–maximum active storage) to the average intensity of water shortages. The finding indicates that most reservoirs in Colorado and Utah currently have high or very high efficiency metrics meaning that these reservoirs are, on average, more than half full while most reservoirs in Texas have low or medium efficiency metrics indicating that these reservoirs are, on average, less than half full. Additionally, the feasibility metrics indicate that reservoir expansion in most western and southern states may not be fruitful because the average annual inflow to reservoirs is less than their maximum active storage over the historical period. Nevertheless, the usefulness metrics show that reservoir expansion can be a useful adaptation strategy to mitigate or attenuate water shortages for some reservoirs in California and Colorado while it cannot considerably decrease the intensity of water shortages in Texas. Findings from this study highlight the utility of the assessment of reservoir expansion at a regional scale considering both available freshwater as an input to reservoirs and the potential water shortage conditions as the main trigger.